Receptors to interleukin-6 and adhesion molecules on circulating monocyte subsets in acute myocardial infarction - Shantsila, Eduard; Tapp, Luke D.; Wrigley, Benjami J.; Montoro-Garcia, Silvia; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2013)
The role of individual monocyte subsets in inflammation and recovery post-myocardial infarction (MI) is insufficiently understood. It was the objective of this study to evaluate the dynamics of monocyte expression of receptors to vascular cell adhesion molecule (VCAM-1r), intercellular adhesion molecule (ICAM-1r), and interleukin-6 (IL-6r) following MI and their relation to inflammatory cytokines, fibrinolytic factors and annexin V-binding microparticles. Expression of VCAM-1r, ICAM-1r, IL-6r on CD14++CD16–(Mon1), CD14++CD16+(Mon2), CD14+CD16++(Mon3) monocyte subsets were quantified by flow cytometry in patients with ST-elevation MI (STEMI, n=50), non-STEMI (n=48) and stable coronary artery disease (n=40). In STEMI, parameters were measured on days 1, 3, 7, 30. On admission with STEMI, VCAM-1r expression was reduced on Mon1 (p=0.007), Mon2 (p=0.036), Mon3 (p=0.005), whilst in NSTEMI there was significant up-regulation of expression by Mon2 (p=0.024) and Mon3 (p=0.049). VCAM-1r on Mon1 correlated positively with plasma IL-1β levels (p=0.001). IL-6r was reduced on Mon2 in acute STEMI, with upregulation of the receptor on Mon1 and Mon2 during follow-up. IL-6r density correlated negatively with plasma levels of tissue-type plasminogen activator (p=0.0005 for Mon1, p=0.001 for Mon2 and Mon3), and positively with annexin V-binding microparticles (p=0.03 for Mon1, p=0.005 for Mon2 and p=0.005 for Mon3). There was no change in monocyte ICAM-1r expression. In conclusion, expression of IL-6r and VCAM-1r is reduced on circulating monocyte subsets involved in inflammatory responses in STEMI. This may represent a regulatory feed-back mechanism aiming to re-balance the marked inflammation which is typically present following acute MI or selective homing of monocytes with high receptor expression to damaged myocardium.Note: The review process for this manuscript was fully handled by Christian Weber, Editor in Chief.
Keywords: Monocytes; monocyte subsets; myocardial infarction; interleukin-6 receptor; intercellular cell adhesion molecule; vascular cell adhesion molecule